Ruthenium NNN complexes with a 2‐hydroxypyridylmethylene fragment for transfer hydrogenation of ketones. (30th October 2017) - Shi, Jing; Shang, Shu; Hu, Bowen; Chen, Dafa
Abstract : Four NNN tridentate ligands L1 –L4 containing 2‐methoxypyridylmethene or 2‐hydroxypyridylmethene fragment were synthesized and introduced to ruthenium centers. When (HOC5 H3 NCH2 C5 H3 NC5 H7 N2 ) (L2 ) and (HOC5 H3 NCH2 C5 H3 NC6 H6 N3 ) (L4 ) reacted with RuCl2 (PPh3 )3, two ruthenium chloride products Ru(L2 )(PPh3 )Cl2 (1 ) and Ru(L4 )(PPh3 )Cl2 (2 ) were isolated, respectively. Reactions of (MeOC5 H3 NCH2 C5 H3 NC5 H7 N2 ) (L1 ) and (MeOC5 H3 NCH2 C5 H3 NC6 H6 N3 ) (L3 ) with RuCl2 (PPh3 )3 in the presence of NH4 PF6 generated two dicationic complexes [Ru(L1 )2 ][PF6 ]2 (3 ) and [Ru(L3 )2 ][PF6 ]2 (4 ), respectively. Complex 1 reacted with CO to afford product [Ru(L2 )(PPh3 )(CO)Cl][Cl]. The catalytic activity for transfer hydrogenation of ketones was investigated. Complex 1 showed the highest activity, with a turnover frequency value of 1.44 × 10 3  h −1 for acetophenone, while complexes 3 and 4 were not active. Abstract : Several metal–ligand cooperative ruthenium complexes bearing NNN tridentate ligands show high activity for transfer hydrogenation of ketones.